Peran Pengajian Al Hidayah Dalam Membangun Interaksi Sosial Di Desa Paya Gambar Kecamatan Batang Kuis Kabupaten Deli Serdang - Annisa Tanjung, Fitri; Abdul Muin , Mohd. Iqbal (Jayapangus Press, 2025)
Social interaction is a basic human need as a social being. In Paya Gambar Village, Al Hidayah religious studies are not only a place for religious learning, but also to strengthen social relations and strengthen Islamic brotherhood. Although the majority of the community is Muslim, many still do not have a good understanding of religion, so religious studies play a role as a strategy to increase religious insight. The purpose of this study is to understand how Al-Hidayah religious studies contribute to the development of social interaction in the community and maintain friendships that strengthen relationships between residents. The method in this study uses a qualitative approach with descriptive methodology. Data were obtained through interviews, observations, and documentation collection. Data analysis was carried out by means of reduction, presentation, and drawing conclusions. To ensure the validity of the data, the researcher used source triangulation. The results of this study indicate that the religious studies facilitate members to get to know each other better, both in aspects of worship and daily life, and deepen religious knowledge. This activity also encourages a sense of togetherness, helps in solving small problems, and provides support when facing difficult economic situations or disasters. Thus, Al-Hidayah religious studies have proven to play an important role as a foundation for strengthening social relations among the residents of Paya Gambar Village, while also functioning as a means of communication and networking in various aspects of social life, religion, and other activities in society.